A two-dimensional three-level sustainability framework for achieving short- and long-term gains: empirical evidence from the Chinese automotive sector - Wu, Lin (2016)
A topic of academic research and business practice which has grown in importance recently is sustainability. Its main objective is to ensure the development of the current generation and protect the right of future generations to prosper. In the business context, sustainability should be reflected in firms’ efforts to simultaneously ensure short- and long-term gains. A time dimension is thus an important feature in the concept of sustainability. In the past two decades, sustainability research specific to operations management has gained popularity. A number of operational practices from the lean, green and social management systems have proven to be effective sustainability practices with acknowledged positive effects on various dimensions of a firm’s sustainability performance. However, a review of existing studies suggests that a time dimension is totally missing in sustainability discussions. Based on the time dimension, there is a need to classify popular sustainability practices based on their effect on performance, another issue which has yet to be addressed. Furthermore, existing sustainability studies in the field of operations management have mainly focused on sustainability practices and performance, ignoring the role of capabilities in interacting with practices to achieve better sustainability performance. This is surprising given that capability is increasingly proven to be the real source of superior firm performance and competitive advantage. This study attempts to address these research gaps by classifying the popular sustainability practices using a time dimension of short- and long-term sustainability, and by examining the role of two important operational capabilities, namely, operational improvement and innovation, in influencing sustainability. Since operational improvement and innovation capabilities involve short-term incremental and long-term radical changes to existing processes, they fit perfectly in the sustainability context featured by the time dimension. Among industry sustainability is a serious concern in the production and consumption stages of the automotive sector. Any negative impact is more severe in emerging economies due to the lack of advanced technologies and management methods compared with developed countries. This study focuses on sustainability issues in the production stage of automotive products in the context of the largest emerging economy in the world, China. China has been the world’s biggest automotive producer and consumer since 2009. Unsustainable problems such as increased costs, environmental pollutions, and human-related issues become more prominent as the industry expands. Thus, the sustainable development of the automotive industry in China deserves attention and this study attempts to address this from an internal operational perspective. Thus, the study aims to develop and empirically validate a two-dimensional three-level sustainability framework that incorporates both short- and long-term sustainability practices, operational improvement and innovation capabilities, and short- and long-term sustainability performance. The categorization of short- and long-term sustainability is based on the traditional Chinese philosophy of duality, Yinyang. Based on relevant management theories and empirical case studies, the research framework is developed with sustainability practices being the independent variables, capabilities being the mediators and sustainability performance being the dependent variables. Horizontally, short-term sustainability practices include various lean practices and basic environmental management practices while long-term sustainability practices focus mainly on Corporate Social Responsibility (CSR). Short- and long-term capabilities in this study refer to operational improvement and operational innovation from an incremental-radical perspective. Short-term sustainability performance mainly includes short-term financial performance, while long-term sustainability performance focuses on long-term financial performance achieved from being sustainable as well as corporate social image enhancement. In addition to the comprehensive research framework, direct relationships (practices on performance, practices on capabilities, and capabilities on performance) are also investigated. Mixed methods involving empirical case studies, a large-scale survey, and a workshop for dissemination of research findings were employed for this study. Given the fact that there is not sufficient theoretical information, case studies were conducted for framework development. Validation of the framework is made through 284 valid responses to an empirical survey conducted among Chinese automotive firms, including end assemblers, tier-1 suppliers, and tier-2 suppliers. Survey data are analyzed using Structural Equation Modelling (SEM). Findings suggest that the implementation of short-term sustainability practices has positive effects on the development of both operational improvement and innovation capabilities. It is also found to significantly improve both short- and long-term sustainability performance. On the other hand, the implementation of long-term sustainability practices is significantly related with the development of operational improvement capability and long-term sustainability performance only. Both forms of capabilities, operational improvement and innovation, are found to partially mediate the relationship between sustainability practices and performance. The findings were disseminated among practitioners on a subsequent workshop, where extensive acknowledgement was received. This study makes theoretical contributions by adding the time dimension to the concept of sustainability and proposing a direction for future empirical sustainability research on how to incorporate the time feature. Furthermore, it contributes to the static sustainability theories of the Resource-based View (RBV) and the Practice-based View (PBV) by clarifying the tacit and explicit ways in which operational practices enhance performance. Thus, the RBV and the PBV can be integrated. In addition to environmental sustainability, the study extends the Nature Resource-based View (NRBV), another static sustainability theory, to a holistic sustainability context. Finally, it confirms the dynamic sustainability theory, the Dynamic Capabilities View (DCV), by confirming the unique role firm capabilities (operational improvement and innovation) play in sustainability. Practically, the findings suggest to companies that the long-term aspect of sustainability should never be overlooked, and managers are encouraged to pay closer attention to the development of capabilities when launching sustainability programs.